Prostaglandin analogues and nitric oxide contribution in the treatment of ocular hypertension and glaucoma. (24th May 2018) - Impagnatiello, Francesco; Bastia, Elena; Almirante, Nicoletta; Brambilla, Stefania; Duquesroix, Brigitte; Kothe, Angela C; Bergamini, Michael V W
Abstract : In patients with ocular hypertension or glaucoma, all treatments aim to lower intraocular pressure (IOP) by modulating aqueous humour (AH) production and/or uveoscleral and trabecular meshwork/Schlemm's canal AH drainage. PG analogues are considered to be the 'gold standard' treatment and are the most frequently used IOP‐lowering agents. Recent data support an important role for NO in regulating IOP. Thus, novel PG analogues carrying a NO‐donating moiety were recently advanced. Latanoprostene bunod (LBN) and NCX 470, NO‐donating derivatives of latanoprost and bimatoprost, respectively, are examples of such compounds. LBN ophthalmic solution, 0.024% (Vyzulta™), showed greater IOP‐lowering efficacy compared with that of Xalatan ® (latanoprost ophthalmic solution, 0.005%) or 0.5% timolol maleate in clinical settings. NCX 470 was found to be more effective than bimatoprost in animal models of ocular hypertension and glaucoma. Selective EP2 receptor agonists (i.e. taprenepag isopropyl, omidenepag isopropyl and aganepag isopropyl) and non‐selective prostanoid receptor agonists (i.e. ONO‐9054, sepetaprost isopropyl) that concomitantly stimulate FP and EP3 receptors have also been shown to hold promise as effective IOP‐lowering agents. Linked Articles: This article is part of a themed section on Eicosanoids 35 years from the 1982 Nobel: where are we now? To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.8/issuetoc